Synchronized navigation and comparative analyses across Ensembl complete bacterial genomes with INSYGHT - Lacroix, Thomas (Bioinformatics, 2016)
Motivation: High-throughput sequencing technologies provide access to an increasing number of bacterial genomes. Today, many analyses involve the comparison of biological properties among many strains of a given species, or among species of a particular genus. Tools that can help the microbiologist with these tasks become increasingly important. Results: Insyght is a comparative visualization tool whose core features combine a synchronized navigation across genomic data of multiple organisms with a versatile interoperability between complementary views. In this work, we have greatly increased the scope of the Insyght public dataset by including 2688 complete bacterial genomes available in Ensembl thus vastly improving its phylogenetic coverage. We also report the development of a virtual machine that allows users to easily set up and customize their own local Insyght server. Availability and implementation: http://genome.jouy.inra.fr/Insyght Contact: Thomas.Lacroix@jouy.inra.fr